Clinical Outcomes of Pregnant and Postpartum Extracorporeal Membrane Oxygenation Patients. Issue 3 (25th September 2021) - Lankford, A.S.; Chow, J.H.; Jackson, A.M.; Wallis, M.; Galvagno, S.M.; Malinow, A.M.; Turan, O.M.; Menaker, J.A.; Crimmins, S.D.; Rector, R.; Kaczorowski, D.; Griffith, B.; et al.
Abstract : ( Anesth Analg . 2021;132:777–787) Cardiovascular issues account for more than one third of pregnancy-related deaths in the United States. Extracorporeal membrane oxygenation (ECMO) is used to treat patients in shock, with hypoxemic and hypercapnic acute respiratory failure, acute respiratory distress syndrome (ARDS), and massive pulmonary embolism (PE), among others. Pregnancy involves unique etiologies of cardiopulmonary failure like amniotic fluid embolism, preeclampsia, and postpartum hemorrhage. There is little data on ECMO in pregnancy, and even a lack of data on the mortality benefit of venoarterial (VA) or venovenous (VV) ECMO in nonpregnant patients with cardiopulmonary arrest, ARDS, and massive PE. This study explored long-term cardiopulmonary outcomes in patients who received peripartum ECMO treatment.